Global prevalence of mutation in the mgrB gene among clinical isolates of colistin-resistant Klebsiella pneumoniae: a systematic review and meta-analysis - Khoshbayan, Amin; Narimisa, Negar; Elahi, Zahra; Bostanghadiri, Narjess; Razavi, Shabnam; Shariati, Aref (Frontiers in Microbiology, 2024)
Background: Colistin is used as a last resort for the managing management of infections caused by multidrug-resistant bacteria. However, the high emergence of colistin-resistant strains has restricted the clinical use of this antibiotic in the clinical setting. In the present study, we evaluated the global prevalence of the mutation in the mgrB gene, one of the most important mechanisms of colistin resistance, in Klebsiella pneumoniae. Methods: Several databases, including Scopus, Medline (via PubMed), and Web of Science, were searched (until August 2023) to identify those studies that address the mgrB mutation in clinical isolates of K. pneumoniae. Using Stata software, the pooled prevalence of mgrB mutation and subgroup analyses for the year of publication, country, continent, mgrB mutation types, and detection methods of mgrB mutation were analyzed. Results: Out of the 115 studies included in the analysis,Among the included 115 studies, the prevalence of mgrB mutations in colistin-resistant K. pneumoniae isolates was estimated at 65% of isolates, and mgrB variations with insertional inactivation had the highest prevalence among the five investigated mutations with 69%. The year subgroup analysis indicated an increase in mutated mgrB from 46% in 2014 to 61% in 2022. Europe had the highest prevalence of mutated mgrB at 73%, while Africa had the lowest at 54%.Europe, with 73%, had the highest prevalence of mutated mgrB, and Africa, with 54%, had the lowest. Conclusion: Mutations in the mgrB gene are reported as one of the most common mechanisms of colistin resistance in K. pneumoniae, and the results of the present study showed that 65% of the reported colistin-resistant K. pneumoniae had a mutation in this gene.